Visual symptoms in Parkinson's disease and Parkinson's disease dementia - Archibald, Neil K.; Clarke, Mike P.; Mosimann, Urs P.; Burn, David J. (Movement disorders, 2011)
Visual symptoms are common in PD and PD dementia and include difficulty reading, double vision, illusions, feelings of presence and passage, and complex visual hallucinations. Despite the established prognostic implications of complex visual hallucinations, the interaction between cognitive decline, visual impairment, and other visual symptoms remains poorly understood. Our aim was to characterize the spectrum of visual symptomatology in PD and examine clinical predictors for their occurrence. Sixty‐four subjects with PD, 26 with PD dementia, and 32 age‐matched controls were assessed for visual symptoms, cognitive impairment, and ocular pathology. Complex visual hallucinations were common in PD (17%) and PD dementia (89%). Dementia subjects reported illusions (65%) and presence (62%) more frequently than PD or control subjects, but the frequency of passage hallucinations in PD and PD dementia groups was equivalent (48% versus 69%, respectively; P = 0.102). Visual acuity and contrast sensitivity was impaired in parkinsonian subjects, with disease severity and age emerging as the key predictors. Regression analysis identified a variety of factors independently predictive of complex visual hallucinations (e.g., dementia, visual acuity, and depression), illusions (e.g., excessive daytime somnolence and disease severity), and presence (e.g., rapid eye movement sleep behavior disorder and excessive daytime somnolence). Our results demonstrate that different “hallucinatory” experiences in PD do not necessarily share common disease predictors and may, therefore, be driven by different pathophysiological mechanisms. If confirmed, such a finding will have important implications for future studies of visual symptoms and cognitive decline in PD and PD dementia. © 2011 Movement Disorder Society